ARTIFICIAL INTELLIGENCE IN INFORMATION TECHNOLOGY - SIKENDER MOHSIENUDDIN MOHAMMAD (International Journal of Innovations in Engineering Research and Technology, 2021)
Artificial Intelligence is a broad field that encompasses various concepts in Information Technology. This research paper focuses on different technologies in AI and how they apply to improve the performance of multiple sectors. The purpose of this study is to discuss Artificial Intelligence and its present and future applications. AI is the foundation of multiple concepts, such as computing, software creation, and data transmission. The technologies that use AI are machine learning, deep learning, Natural Language Generation, speech recognition, robotics, and biometric identification. AI applies to many sectors such as healthcare sectors, assembling and manufacturing industries, business organizations, and in the automotive industries. AI also has various advantages that make it gain more popularity in many areas. The AI-powered machine can perform many jobs at once; they are not costly compared to human beings and are accurate and efficient. AI also encounters multiple problems that undermine its application. AI is prone to technical difficulties, security snags, data difficulties, and can cause accidents if users fail to understand the AI system. The increased use of AI has transformed various sectors by boosting the organization’s performance and facilitating data safety.